2014
DOI: 10.2215/cjn.04660514
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Circulating Markers to Predict Bone Loss across the CKD Spectrum

Abstract: Patients with CKD are at increased risk of bone loss and fractures. Prospective observational studies have shown that the severity of kidney disease is directly associated with the amount of bone loss (1-4). In CKD, fractures are 2-to 14-fold more common than in the general population (5,6). The frequency of fractures increases as renal disease worsens (7,8), and the incidence of fractures has increased over the past 20 years (9,10). Compared with those without fractures, patients with CKD with fractures exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The usefulness of DXA to classify fracture risk in CKD patients has been controversial because the pathogenesis of renal osteodystrophy is not uniform and may be the result of multiple causes, and BMD measured by DXA does not provide information about the type of renal osteodystrophy [ 22 ]. Some past studies with small sample sizes showed that BMD measured by DXA could not be used to identify the fracture risk in hemodialysis patients [ 23 , 24 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The usefulness of DXA to classify fracture risk in CKD patients has been controversial because the pathogenesis of renal osteodystrophy is not uniform and may be the result of multiple causes, and BMD measured by DXA does not provide information about the type of renal osteodystrophy [ 22 ]. Some past studies with small sample sizes showed that BMD measured by DXA could not be used to identify the fracture risk in hemodialysis patients [ 23 , 24 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, progressive CKD is generally associated with increased levels of PTH, fibroblast growth factor 23 (FGF‐23), osteoprotegerin, sclerostin, and Dickkopf‐related protein 1 (DKK1) and reductions in α‐Klotho, serum 25‐hydroxyvitamin D [25(OH)D], and [1,25(OH) 2 D] . The expression of bone turnover such as bone‐specific alkaline phosphatase (BSAP), procollagen type 1 N‐terminal (P1NP), C‐terminal telopeptide of type 1 collagen (CTX), and tartrate‐resistant acid phosphatase (TRAP‐5b) is more variable and dependent not only on the degree of renal impairment but also bone turnover . Together, these changes impact bone formation, resorption, and mineralization through their effects on osteoblast and osteocyte function.…”
Section: Pathophysiology Of Renal Osteodystrophymentioning
confidence: 99%
“…Several other recent papers have shown that low BMD actually predicts fracture in dialysis and renal transplant patients 90, 91. The use of micro‐computerized tomography might also be a useful tool for the estimation of bone loss and micro‐architectural changes; however, they need further evaluation in CKD 92. Overall, although there have been uncertainties concerning the utility of BMD in CKD,93 BMD measure may become useful in this population.…”
Section: Bone and Musculoskeletal Abnormalities In Chronic Kidney Dismentioning
confidence: 99%
“…90,91 The use of micro-computerized tomography might also be a useful tool for the estimation of bone loss and micro-architectural changes; however, they need further evaluation in CKD. 92 Overall, although there have been uncertainties concerning the utility of BMD in CKD, 93 BMD measure may become useful in this population. This issue is currently under review, 94 and it is likely that BMD testing could be suggested in CKD patients with evidence of CKD-MBD and/or risk factors for osteoporosis, if results may affect treatment decisions.…”
Section: Alteration Of Bone Mass In Chronic Kidney Diseasementioning
confidence: 99%